PENGARUH PUPUK ORGANIK (Azolla pinnata) TERHADAP C-ORGANIK TANAH, SERAPAN N DAN BOBOT KERING TANAMAN PADI (Oryza sativa L.) PADA TANAH DENGAN TINGKAT SALINITAS TINGGI - Mayang Sunduz Arafah; Mieke Rochimi Setiawati; Anne Nurbaity (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
Utilizing organic fertilizer Azolla pinnata is needed especially for rice commodity which planted in salin soil in coast area for increasing the efficiency of inorganic fertilizer by adding organic matters. This research was aimed to get the best combination of utilizing organic fertilizer Azolla pinnata to increase total organic carbon, nitrogen uptake, and dry weight of rice in saline soil. This research used Randomized Complete Block Design experiment which consisted of eight combinations of treatment. Those are treatment of salinity 0, 2, 4 and 6 mmhos cm-1 + without utilizing organic fertilizer Azolla pinnata and treatment of salinity 0, 2, 4, and 6 mmhos cm-1 + utilizing organic fertilizer Azolla pinnata. The result showed that utilizing organic fertilizer Azolla pinnata can reduce the negative effect from salinity which proven by increased N uptake of rice in treatment of salinity 6 mmhos cm-1.Keywords: Azolla pinnata, Rice (Oryza sativa L.), Soil with high salinity level